Analysis of Service Quality on Patient Satisfaction in the Psychiatric Outpatient Clinic at Aek Kanopan Regional General Hospital - David Erickson Simanjuntak; Chrismis Novalinda Ginting; Masryna Siagian (Jurnal Ners, 2026)
Abstract Service quality is a key determinant of patient satisfaction and hospital performance. In psychiatric settings, satisfaction depends not only on clinical competence but also on empathy, communication, and responsiveness. This study aimed to analyze the relationship between service quality and patient satisfaction among psychiatric outpatients at Aek Kanopan Regional General Hospital, North Sumatra. This quantitative descriptive–analytic study used a cross-sectional design. A total of 150 outpatients were selected using accidental sampling. Data were collected using a SERVQUAL questionnaire with five dimensions—tangibility, reliability, responsiveness, assurance, and empathy—rated on a five-point Likert scale. Validity and reliability tests yielded Cronbach’s α = 0.977. Data analysis employed descriptive statistics, Pearson correlation, and simple linear regression with a significance level of p < 0.05. The mean perception score (17.05) was lower than the mean expectation score (18.48), producing an average negative GAP of –1.43, indicating unmet patient expectations. The largest gap occurred in reliability (–3.26), followed by tangibility (–2.56), responsiveness (–1.31), and empathy (–0.34), while assurance showed a small positive GAP (+0.11). Correlation tests revealed that responsiveness and empathy were positively and significantly associated with patient satisfaction (r = 0.027 and r = 0.001, respectively; p < 0.05). Overall, psychiatric outpatients at RSUD Aek Kanopan were dissatisfied with most dimensions of service quality. Enhancing reliability, responsiveness, and empathy, while maintaining strong assurance performance, is essential to improving patient satisfaction and the overall quality of mental health services. Keyword: Service Quality, Patient Satisfaction, SERVQUAL, Psychiatry Outpatient, Hospital Services